Study on the Curcumin dynamics and distribution through living biofilms - Carvalho, Mariana T.; Dovigo, Lívia Nordi [UNESP]; Rastelli, Alessandra N. S. [UNESP]; Bagnato, Vanderlei S. (SPIE, the international society for optics and photonics, 2013)
Human oral cavity is colonized by a wide range of microorganisms, often organized in biofilms. These biofilms are responsible for the pathogenesis of caries and most periodontal diseases. A possible alternative to reduce biofilms is the photodynamic inactivation (PDI). The success of the PDI depends on different factors. The time required by the PS to remain in contact with the target cells prior to illumination is determinant for the technique's efficacy. This study aimed to assess the interaction between the PS and the biofilm prior to the PDI. We used confocal microscopy and FLIM to evaluate the interaction between the PS and the biofilm's microorganism during the pre-irradiation time (PIT). The study of this dynamics can lead to the understanding of why only some PSs are effective and why is necessary a long PIT for some microorganisms. Our results showed that are differences for each PIT. These differences can be the determinate for the efficacy of the PDI. We observed that the microorganism needs time to concentrate and/or transport the PS within the biofilm. We presented preliminary results for biofilms of Candida albicans and Streptococcus mutans in the presence of Curcumin and compared it with the literature. We observed that the effectiveness of the PDI might be directly correlated to the position of the PS with the biofilm. Further analyses will be conducted in order to confirm the potential of FLIM to assess the PS dynamics within the biofilms. © 2013 SPIE.
Keywords: Candida albicans; Confocal Microscopy; Curcumin; Fluorescence lifetime imaging; Oral Biofilm; Photodynamic Inactivation; Photosensitizer; Streptococcus mutans; Photodynamic inactivation; Candida; Confocal microscopy; Dynamics; Microorganisms; Photosensitizers; Yeast; Biofilms